Dental prosthetic status and prosthetic needs of institutionalized elderly population in Mangalore, Karnataka, India - Vijaya Hegde; R Pandya Sajankumar (Wolters Kluwer Medknow Publications, 2017)
Aim: To assess the data regarding dental prosthetic status and prosthetic needs of institutionalized elderly living in geriatric homes of Mangalore, Karnataka, India. Materials and Methods: A cross-sectional survey was conducted among institutionalized elderly living in geriatric homes in Mangalore. The sample size was estimated to be 300. The information related to sociodemographic data, prosthetic status, and prosthetic need was obtained using the WHO Oral Health Assessment Form 1997. Chi-square test was used to analyze the data. Results: Out of 300 elderly people, 94 were males and 206 were females. The study results showed that 53.1% and 60.45% of the total subjects had no prostheses in upper and lower arch, respectively. The study also revealed that the need for full prostheses was more among females compared to males. Conclusion: The present study concludes that need for prosthesis was high among the institutionalized elderly.